Marine-derived Anti-tuberculosis Compounds - Masand, Mukesh; Sharma, Pramod Kumar; Balaramnavar, Vishal M. (Natural Products Journal, The, 2025)
Tuberculosis (TB), which is caused primarily by Mycobacterium tuberculosis, is the largest cause of death among all infectious diseases, accounting for more than two million fatalities each year. Marine natural products and some of their derivatives have been found to have potent anti-tubercular activity against Mycobacterium TB, and some of them have been chosen as prototype molecules for the development of novel anti-tubercular drugs. Because of their strong medicinal qualities, a variety of marine natural products such as terpenoids, alkaloids, pyrones, sterols, and quinones derived from marine sources have piqued interest in recent decades. In this review study, we present current discoveries on the anti-tubercular action of marine natural products, emphasizing their medicinal potential for the treatment of tuberculosis. Based on the research from the last decade, this review provides a full grasp of marine natural products as anti-tubercular agents, as well as a plausible mechanism of action.
Keywords: Tuberculosis